PERBANDINGAN KONTRAK JUAL BELI ELEKTRONIK MENURUT HUKUM POSITIF DAN HUKUM ISLAM - Arso, Dimas Dwi; Edytiawarman, Edytiawarman; Muljono, Slamet (Penerbit Universitas Atma Jaya Yogyakarta, 2021)
The purpose of this research is to find out and analyze the provisions of Islamic Law in buying and selling transactions in electronic contracts as well as legal protection of the parties in buying and selling transactions via electronic. Normative legal research is used in this study, because this research will examine and analyze various laws and regulations concerning sale and purchase agreements made via electronic based on positive law and Islamic law. The results of the research, namely agreements or transactions electronically in Indonesia, have generally been regulated by positive law, in particular the provisions regarding the engagement set out in Book III of the Civil Code and the Agreement in general, and are regulated in the electronic information and transaction regulation. Whereas in the applicable Islamic law in Indonesia, although this electronic transaction is not specifically regulated, the rules contained in Islamic law can be accommodated in terms of electronic transactions. However, in practice in the field there may be deficiencies related to electronic transaction activities, for example regarding legal protection for consumers / buyers. For this reason, it is necessary to make more specific regulations related to legal protection in terms of electronic transactions, considering that the electronic trading system is always increasing its transaction activities and it is necessary to establish an association of merchants / sellers electronically, especially sellers who use social networking media, so that parties merchand is more detectable.